Evaluadores del Volumen 35(2) - Runa . (RUNA, archivo para las ciencias del hombre, 1970)
Evaluadores ExtranjerosRuy Llera Blanes – University of Bergen, NoruegaJosep Martí – Institució Milà i Fontanals /CSIC, EspañaEnrique Cámar de Landa – Universidad de Valladolid, EspañaOsvaldo Meira Trigueiro – Universidade Federal da Paraíba,BrasilPaola Ponce - Durham University, InglaterraEvaluadores NacionalesNicolas Viotti – UCA / CONICETJorge Suby – Dep. Arq. UNCPBAAna Ramos – IIDyPCA, UNRN / CONICETClaudia Salomon Tarquini – IES, UNLPam / CONICETMirta Bialogorski – Museo de Arte Popular José Hernández / GCBAGraciela Bailliet – IMBICE/ CONICETNoemí Acreche – UNSa